Efficacy and Safety of Ultrasound-Guided Radiofrequency Treatment for Chronic Pain in Patients with Knee Osteoarthritis: A Systematic Review and Meta-Analysis - Yuzhao Huang; Qiufang Deng; Liuqing Yang; Jiahui Ma; Ziyang Wang; Dong Huang; Ling Luo; Haocheng Zhou (Pain Research and Management)
Background. Knee osteoarthritis (KOA) is a common degenerative disease associated with joint dysfunction and pain. Ultrasound-guided radiofrequency (RF) may be a promising therapy in the treatment of chronic pain for KOA patients. Objective. To evaluate the efficacy and safety of ultrasound-guided RF treatment for chronic pain in patients with KOA. Design. A systematic review was conducted, and a meta-analysis was carried out when possible. Setting. We examined the studies evaluating the clinical efficiency of ultrasound-guided RF on chronic pain in KOA population. Method. A systematic review for the efficacy and safety of ultrasound-guided RF treatment for pain management of KOA patients was carried out in PubMed, EMBASE, Cochrane Library, Web of Science, Wanfang Data, and China National Knowledge Infrastructure (CNKI) from the date of inception to February 2020, and a meta-analysis was conducted. The primary outcomes of pain intensity (visual analogue scale or numerical rating scale) and knee function [the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC)] were evaluated from baseline to various follow-up times by random-effects model. Heterogeneity was assessed by I2 statistic and the potential sources of heterogeneity by subgroup and metaregression analyses, respectively. Results. Eight publications with 256 patients were included in the meta-analysis. RF could relieve pain with −4.196 of pooled mean difference and improve knee function by decreasing 23.155 points in WOMAC. Three patients had ecchymosis, two with hypoesthesia and one with numbness after the procedure, and improved within 6 months. Furthermore, study design and treatment target were the sources of heterogeneity by subgroup and metaregression analyses, accounting for 37% and 74% of variances, respectively. Target of genicular nerve achieved better pain relief than intra-articular or sciatic nerve. Sensitivity analysis showed that removal of any single study was unlikely to overturn the findings. Limitations. There were some limitations in the study. Firstly, the small number of relevant studies limited the confidence level of the meta-analysis. Also, the significant heterogeneity may not be explained due to the limited data. Secondly, the direct comparison of two different guidance methods (ultrasound vs. fluoroscopy) for RF therapy is lacking. In addition, the outcomes were blindly assessed in the meta-analysis from all studies according to evaluation of bias, which could affect the reality of the data. Finally, most of the studies only provided short follow-up times, so we could not analyze the long-term effectiveness of ultrasound-guided RF in the treatment of patients with KOA. Conclusions. Ultrasonography is an effective, safe, nonradiative, and easily applicable guidance method for RF in pain relief and functional improvement in KOA patients.